A paramagnetic photo-Fenton catalyst, a preparation method and application thereof

CN122917261APending Publication Date: 2026-10-16GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610854814.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0010]本发明提供一种顺磁性光自芬顿催化剂及其制备方法和应用,旨在解决现有芬顿和光芬顿技术中需要外加H2O2、Fe2+易流失、pH适用范围窄、H2O2生成与活化协同受阻等技术难题,实现高效、经济、环境友好的有机污染物降解

Benefits of technology

(1)H2O2生成与活化一体化:在同一催化剂上同时实现H2O2的原位生成和快速活化,无需外加H2O2,降低成本和操作复杂度,H2O2利用率高;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917261A_ABST
    Figure CN122917261A_ABST
Patent Text Reader

Abstract

The application provides a paramagnetic light self-Fenton catalyst and a preparation method and application thereof, and belongs to the technical field of photocatalysts. The preparation method of the paramagnetic light self-Fenton catalyst comprises the following steps: placing a ferrocene derivative, formaldehyde and m-dihydroxybenzene in a mixed solvent of ethanol and water, adding a catalyst, stirring to obtain a precursor solution; transferring the precursor solution to a high-pressure reaction kettle to perform a solvothermal polycondensation reaction; after the reaction is completed, cooling, filtering, washing and drying are performed, and thus the paramagnetic light self-Fenton catalyst functionalized by ferrocene is obtained. The catalyst is obtained by copolymerization of the ferrocene derivative, the m-dihydroxybenzene and the formaldehyde, realizes the integration of in-situ generation and activation of H2O2, has the advantages of wide pH application range, no iron ion dissolution, visible light response and high degradation efficiency, and can be widely used in photocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, specifically relating to a paramagnetic photocatalyst, its preparation method, and its application. Background Technology

[0002] With the acceleration of industrialization and urbanization, the large-scale emission of recalcitrant organic pollutants such as dyes, antibiotics, and endocrine disruptors poses a severe challenge to ecological security. Developing efficient, economical, and environmentally friendly water treatment technologies has become an urgent need in the environmental field.

[0003] With Fe 2+ While the traditional Fenton technique, which uses the catalytic generation of hydroxyl radicals (·OH) from H₂O₂, is widely used, it has significant drawbacks: (1) pH constraint and iron sludge problem: The optimal reaction environment is limited to a pH environment of 2-4. Under neutral conditions, Fe(OH)3 precipitate is easily formed, which leads to catalyst deactivation and produces a large amount of difficult-to-treat chemical iron sludge.

[0004] (2) Operating costs and safety hazards: Additional H2O2 needs to be added, which poses high risks in transportation and storage. Excessive H2O2 can trigger elimination reactions and reduce oxidation efficiency.

[0005] (3) Slow catalytic cycle: Fe 3+ Reduced to Fe 2+ The rate of reaction is extremely slow, becoming a bottleneck that limits the overall reaction rate.

[0006] To address these issues, researchers have developed supported heterogeneous catalysts (such as Fe-MOF and Fe-zeolite). While these catalysts reduce iron loss, they still face challenges such as low utilization of active sites, high iron leaching and mass transfer resistance under acidic conditions, and still rely on the addition of H2O2.

[0007] Photo-Fenton technology introduces light-induced Fe 2+ Reduction improves efficiency, but it still relies on the addition of H2O2. Emerging photocatalytic Fenton technology aims to achieve integrated "generation-activation" by photocatalyzing in-situ H2O2 generation and simultaneously activating hydroxyl radicals (·OH). Current research focuses primarily on semiconductor / iron composite systems (such as TiO2 / Fe3O4) or organic polymers. However, the in-situ H2O2 generation rate of photocatalysts is typically below 500 μmolg. -1 h -1 The efficiency of in-situ H2O2 generation remains the core bottleneck restricting the efficiency of photo-Fenton conversion, mainly due to the following reasons: (i) The generation of H2O2 is spatially and temporally separated from the activation site, resulting in low utilization of intermediate products.

[0008] (ii) Proton transfer is hindered. The photocatalytic reduction of O2 to H2O2 involves the electron-proton coupling transfer (PCET) process. Although resorcinol-formaldehyde resin (RF) has abundant phenolic hydroxyl groups, it is bound by hydrogen bonds, resulting in a high proton dissociation energy barrier, which limits the PCET efficiency.

[0009] Ferrocene (Fc) possesses a stable sandwich structure, reversible redox properties, and a strong electron-donating ability. Its Fe... 2+ The center is protected by organic ligands, making it less prone to loss over a wide pH range and exhibiting Fenton activity. However, systematic research is still lacking on how to organically combine ferrocene with photocatalytic materials (such as RF resins) to break hydrogen bond binding and improve proton dissociation efficiency, and to construct an efficient integrated H2O2 generation-activation system. Summary of the Invention

[0010] This invention provides a paramagnetic photo-Fenton catalyst, its preparation method, and its application, aiming to solve the problem that existing Fenton and photo-Fenton technologies require the addition of H2O2 and Fe. 2+ Overcoming technical challenges such as easy loss, narrow pH range, and hindered synergistic effect of H2O2 generation and activation, we can achieve efficient, economical, and environmentally friendly degradation of organic pollutants.

[0011] To solve the above-mentioned technical problems, the present invention is implemented as follows: A method for preparing a paramagnetic photo-self-Fenton catalyst includes the following steps: Step S1: Ferrocene derivative, formaldehyde and resorcinol are placed in a mixed solvent of ethanol / water in a mass ratio, a catalyst is added, and the mixture is stirred until completely dissolved to obtain a precursor solution. Step S2: The precursor solution is transferred to a high-pressure reactor for solvothermal polycondensation reaction; Step S3: After the reaction is complete, cool to room temperature, filter to collect the solid product, and wash to remove unreacted monomers and oligomers; Step S4: Dry the washed solid to obtain a ferrocene-functionalized paramagnetic photo-self-Fenton catalyst.

[0012] As a preferred improvement, the ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde; the catalyst is one of oxalic acid and acetic acid, and the amount used is 0.1-0.3% of the mass of resorcinol.

[0013] As a preferred improvement, the ratio of ethanol to water in the mixed solvent is 1:5 to 1:15.

[0014] As a preferred improvement, the ferrocene derivative accounts for 1%-10% of the total mass of the reactants; the mass ratio of the ferrocene derivative to resorcinol is 1:5-1:30; and the mass ratio of resorcinol to formaldehyde is 1:2.

[0015] As a preferred improvement, in step S2, the temperature of the solvothermal polycondensation reaction is 250°C and the time is 6-24 hours.

[0016] As a preferred improvement, in step S3, the washing process involves washing with deionized water and ethanol 3-5 times in sequence.

[0017] As a preferred improvement, in step S4, the drying process is carried out under vacuum conditions at 60-100°C for 8-24 hours.

[0018] A paramagnetic photo-self-Fenton catalyst was prepared using the method described above.

[0019] An application of the paramagnetic photo-self-Fenton catalyst as described above involves dispersing the paramagnetic photo-self-Fenton catalyst in an aqueous solution containing organic pollutants. Under visible light or sunlight irradiation, the catalyst generates H2O2 in situ and simultaneously activates to produce hydroxyl radicals, thereby degrading organic pollutants through a photo-self-Fenton reaction.

[0020] As a preferred improvement, the organic pollutants include dyes, antibiotics, phenols, and pesticides.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) Integrated generation and activation of H2O2: In-situ generation and rapid activation of H2O2 are achieved simultaneously on the same catalyst, without the need for external H2O2, reducing costs and operational complexity, and achieving high utilization of H2O2. (2) Fe is stably fixed and does not leak: Ferrocene is embedded in the RF resin framework through C-C covalent bonds, and Fe... 2+ It is firmly protected by organic ligands and does not dissolve in the pH range of 3-9 (leaching rate <0.2mg / L), which is far superior to traditional Fenton catalysts; (3) Wide pH range: Due to Fe 2+ Protected by organic ligands, and with the protons in the H2O2 synthesis process originating from the dissociation of phenolic hydroxyl groups, it is water-independent and the catalyst maintains high activity in the pH range of 3-9, thus broadening its application scope. (4) Visible light driven: The catalyst responds well to visible light (λ≥420nm), can utilize sunlight, and is suitable for practical applications; (5) High degradation efficiency: The degradation rate of various organic pollutants (dyes, antibiotics, phenols, pesticides, etc.) can reach 85-98%, the mineralization rate is 60-80%, and the reaction time is 1-4 hours; (6) Simple preparation and low cost: The one-step solvothermal polycondensation method is adopted, which does not require complicated post-processing. The raw materials are readily available and the cost is low (<20 yuan / g). Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 Scanning electron microscope image showing the paramagnetic photo-self-Fenton catalyst of Example 1; Figure 2 The particle size distribution curve of the paramagnetic photo-self-Fenton catalyst in Example 1 is shown. Figure 3 This shows the TEM and elemental mapping diagrams of the paramagnetic photo-self-Fenton catalyst of Example 1. Figure 4 The graph shows the hysteresis loop (MH curve) of the paramagnetic photo-self-Fenton catalyst in Example 1; Figure 5 A comparison of the curves for long-term H2O2 production in pure RF and RF-doped with 5% Fc. Figure 6 This graph shows a comparison of the catalytic degradation results of chloroquine phosphate under pure RF and different Fc doping conditions. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] like Figures 1-6 As shown, this embodiment provides a method for preparing a paramagnetic photo-self-Fenton catalyst, comprising the following steps: Step S1: Ferrocene derivative, formaldehyde and resorcinol are placed in a mixed solvent of ethanol / water in a mass ratio, the catalyst is added, and the mixture is stirred for 1-3 hours until completely dissolved to obtain a precursor solution.

[0025] The ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde, and its mass accounts for 1%-10% of the total mass of the reactants; the mass ratio of the ferrocene derivative to resorcinol is 1:5-1:30, preferably 1:10-1:20, and the mass ratio of resorcinol to formaldehyde is 1:2.

[0026] The volume ratio of ethanol to water in the mixed solvent is 1:5 to 1:15.

[0027] The catalyst is oxalic acid or acetic acid, and the amount used is 0.1-0.3% of the mass of resorcinol.

[0028] Step S2: The precursor solution is transferred to a high-pressure reactor, sealed, and heated at 250°C for 6-24 hours to carry out a solvothermal polycondensation reaction.

[0029] Preferably, the solvothermal polycondensation reaction takes 12 hours.

[0030] Step S3: After the reaction is complete, cool to room temperature, filter and collect the solid product, and wash with deionized water and ethanol 3-5 times in sequence to remove unreacted monomers and oligomers.

[0031] Step S4: The washed solid is dried under vacuum at 60-100℃ for 8-24 hours to obtain ferrocene-functionalized RF photo-self-Fenton catalyst.

[0032] In the preparation method of this invention, resorcinol and formaldehyde are subjected to hydroxymethylation and subsequent multi-step polycondensation reactions to construct a rigid three-dimensional cross-linked framework of resorcinol-formaldehyde (RF) resin. To achieve efficient loading of ferrocene, ferrocene derivatives with aldehyde groups (such as ferrocene-formaldehyde) must be used as comonomers. The aldehyde groups in these derivatives act as specific active sites, capable of undergoing in-situ ternary copolymerization with highly active sites (ortho / para) on the benzene ring of resorcinol. Through this mechanism, ferrocene units are firmly and in-situ embedded into the network framework of the RF resin via strong and stable C-C covalent bonds (such as methylene bridges). In this cross-linked network, the ferrocene groups not only exhibit a highly dispersed molecular-level state but also undergo strong electronic coupling with the aromatic rings in the RF resin framework through π-π conjugation and space charge effects, thereby constructing a stable and continuous directional electron transport channel.

[0033] This invention introduces ferrocene into RF resin, utilizing the unique properties of ferrocene to achieve a triple synergistic effect: (1) Electron spin channel construction and proton dissociation promotion Electron-donating effect: The cyclopentadienyl group (Cp) of ferrocene has a strong electron-donating ability, which provides electrons to the π-electron system of RF resin through the σ-π conjugation effect, increasing the electron cloud density of the RF resin skeleton; Electron spin channels: Fe in ferrocene 2+ The center has unpaired electrons (d 6 low spin or d 6 High-spin electrons couple with the π-electron system of RF resin to form an electron spin channel. This spin channel promotes the rapid transfer and separation of photogenerated electrons and reduces electron-hole recombination. Paramagnetic microenvironment: The introduction of ferrocene creates a paramagnetic microenvironment. This microenvironment slightly perturbs the OH bonds of neighboring phenolic hydroxyl groups, reducing their bond energy and promoting proton release, thus providing a sufficient proton source for the subsequent reduction of O2 to H2O2. (2) Improved efficiency of in-situ H2O2 generation Enhanced light absorption: The introduction of ferrocene expands the light absorption range of RF resin, especially the absorption enhancement in the 450-600nm region, which improves the utilization rate of visible light. Enhanced charge separation: The electron spin channel constructed by the paramagnetic microenvironment promotes the selective transfer of photogenerated electrons from the RF resin framework to the ferrocene sites. Through the paramagnetic perturbation effect, intersystem crossing of photogenerated electrons from the singlet state to the long-lived triplet state is induced, effectively prolonging the exciton lifetime, suppressing the nonradiative recombination of electron-hole pairs, and improving the quantum efficiency of the system. Enhanced oxygen reduction activity: Long-lived electrons promote the Fe content of ferrocene. 2+ The redox reaction at the center, with Fe as the active site, can promote the adsorption of O2 and reduce intermediates. Activation energy of OOH; H2O2 formation rate: The H2O2 formation rate of the Fc-RF catalyst is 1000-3000 μmol·g. -1 ·h -1 It is 2-6 times that of pure RF resin.

[0034] (3) In-situ activation of H2O2 and generation of hydroxyl radicals (·OH) Fenton's active center: Fe in ferrocene 2+ The center exhibits Fenton activity and can catalyze the decomposition of H2O2 to generate hydroxyl radicals: H2O2 + Fe 2+ →Fe 3+ +·OH+OH - ; In-situ activation: H2O2 generated in-situ by photocatalysis in ferrocene Fe 2+ The center is immediately activated without needing to diffuse to other sites, achieving an integrated "generation-activation" process.

[0035] This embodiment also provides a paramagnetic photo-self-Fenton catalyst, prepared using the above-described preparation method. The paramagnetic photo-self-Fenton catalyst (Fc-RF catalyst) comprises an RF resin intercalated with ferrocene groups. The RF resin framework provides photocatalytic activity and H2O2 generation capability, while the ferrocene units provide Fe2+ active centers and electronic regulation functions.

[0036] The iron content in the paramagnetic photocatalyst Fenton catalyst is 1-10 wt% (preferably 3-7 wt%). Too low an Fe content results in insufficient active sites; too high an Fe content may cause the ferrocene derivative to aggregate, reducing dispersibility and activity. The mass ratio of the ferrocene derivative to resorcinol is 1:5-1:30 (preferably 1:10-1:20). This ratio ensures the uniform distribution of ferrocene groups within the RF resin framework while maintaining the DA structure of the RF resin, thus enabling it to exhibit visible light photocatalytic activity.

[0037] This embodiment also provides an application of a paramagnetic photo-self-Fenton catalyst, used as a catalyst for the photocatalytic degradation of organic pollutants.

[0038] The catalyst is dispersed in an aqueous solution containing organic pollutants. Under visible light or sunlight irradiation, the catalyst generates H2O2 in situ and is simultaneously activated to produce hydroxyl radicals (·OH), which degrade the organic pollutants through photo-Fenton reaction.

[0039] The photocatalytic reaction conditions are as follows: catalyst dosage 0.1-3.0 g / L, initial pollutant concentration 10-200 mg / L, reaction temperature 15-50℃, pH value 3-9, light source wavelength ≥420 nm, and light intensity 50-200 mW / cm². 2 Under visible light irradiation, the degradation rate of organic pollutants can reach 85-98%, with a reaction time of 1-4 hours.

[0040] The organic pollutants include dyes (rhodamine B, methylene blue, methyl orange, etc.), antibiotics (tetracycline, norfloxacin, sulfonamides, etc.), phenols (phenol, bisphenol A, etc.), pesticides (atrazine, chlorpyrifos, etc.) or other recalcitrant organic compounds.

[0041] The paramagnetic photo-self-Fenton catalyst has the following advantages: (1) In-situ efficient and continuous generation of H2O2, without the need for external H2O2, reducing costs and operational complexity; (2) Fe covalently intercalates, avoiding metal dissolution and expanding the applicable pH range to 3-9, which is superior to the traditional Fenton reaction (pH 2-4). (3) The activity retention rate is >85% after 10 cycles of use; (4) Visible light driven, high solar energy utilization rate, suitable for practical applications.

[0042] The reaction mechanism of the paramagnetic photo-self-Fenton catalyst in the degradation of organic pollutants is as follows: (1) Photogenerated electron-hole pairs are generated under visible light irradiation; (2) The electron-donating properties of ferrocene and the π-electron system of the RF resin skeleton form an electron spin channel, generating a paramagnetic microenvironment, which slightly perturbs the neighboring phenolic hydroxyl groups, lowers the proton dissociation energy barrier, and promotes proton release. (3) Photogenerated electrons undergo electron-proton coupling transfer with protons, participating in the reduction of dissolved oxygen to generate H2O2: O2 + 2H + +2e - →H2O2; (4) In-situ generated H2O2 in ferrocene Fe 2+ The center is activated, generating hydroxyl radicals: H₂O₂ + Fe 2+ →Fe 3+ +·OH+OH - ; (5) Fe 3+ Reduced and regenerated into Fe by photogenerated electrons 2+ To achieve catalytic cycling: Fe 3+ +e - →Fe 2+ ; (6) Hydroxyl radicals oxidize and degrade organic pollutants, eventually mineralizing them into CO2 and H2O.

[0043] Compared to traditional Fenton reactions or simple photocatalytic reactions, the photo-self-Fenton method based on paramagnetic photo-self-Fenton catalysts provided in this invention has the following advantages: degradation rate increased by 2-5 times, mineralization rate increased by 10-20%, pH applicable range broadened to 3-9, and no need for external H2O2 and Fe. 2+ It has the ability to degrade universal organic pollutants.

[0044] Example 1 This embodiment provides a method for preparing a paramagnetic photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO)₂ was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring was continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixture was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by vacuum filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h.

[0045] The sample obtained in Example 1 was examined using a scanning electron microscope, and the resulting microstructure image is shown below. Figure 1 As shown, from Figure 1 It can be seen that the paramagnetic photo-self-Fenton catalyst is consistent with the RF resin, both exhibiting a spherical structure.

[0046] Figure 2 This is a particle size distribution curve of a paramagnetic photo-self-Fenton catalyst, from... Figure 2 It can be seen that the average particle size of the microparticles is 3.53 μm, which is not much different from the particle size of RF (2-5 μm), indicating that the copolymerization and intercalation of Fc has little effect on the morphology and structure of the resin.

[0047] Figure 3 The TEM and elemental mapping images of the paramagnetic photo-self-Fenton catalyst of Example 1 are shown. The TEM shows that the catalyst has a spherical solid structure, and the mapping shows that the Fe element is uniformly distributed in the spheres without obvious aggregated particles.

[0048] Figure 4 The graph shows the hysteresis loop (MH curve) of the paramagnetic photo-self-Fenton catalyst in Example 1. It shows that although the catalyst has weak magnetism (maximum 0.4 emu / g), the S-shaped structure indicates its superparamagnetic properties. That is, without the need for an external magnetic field, the ferrocene center can generate a paramagnetic environment, which slightly perturbs the electron and phenolic hydroxyl bond energies of the adjacent RF framework.

[0049] Figure 5 This graph shows a comparison of long-term H2O2 production curves for pure RF and RF doped with 5% Fc. Figure 5 It can be seen that the H2O2 produced by 5% Fc is twice that of RF, and it continues to increase linearly within 12 hours, with a standard deviation of 2.6% per hour.

[0050] Figure 6 This graph shows a comparison of the catalytic degradation results of chloroquine phosphate under pure RF and different Fc doping conditions. Figure 6 It can be seen that the degradation rate constant of chloroquine phosphate by 5% Fc doping is twice that of RF. The increase in H2O2 production is consistent with the increase in pollutant degradation, indicating that H2O2 is the main factor determining the efficiency of photo-self-Fenton degradation, and also proving the universality of the degradation performance of this paramagnetic photo-self-Fenton catalyst.

[0051] Example 2 This embodiment provides a method for preparing a paramagnetic photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO) was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring was continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixture was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h.

[0052] Example 3 This embodiment provides a method for preparing a paramagnetic photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO)₂ was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixed solution was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 24 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by vacuum filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h.

[0053] Example 4 This embodiment provides a method for preparing a paramagnetic photo-self-Fenton catalyst, comprising the following steps: 0.088 g of Fc-(CHO)₂ was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixture was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h.

[0054] Samples from Examples 1-4 were used for photocatalytic degradation experiments of chloroquine phosphate (CQ). The specific procedure for the photocatalytic degradation experiment is as follows: A 300 W xenon lamp (PLS-SXE300, Beijing Bofeilai) was used as a simulated solar light source, and a 420 nm cutoff filter was applied to obtain visible light (λ ≥ 420 nm). The irradiance of the light source was 100 mW cm⁻¹. ⁻2 The distance between the light source and the liquid surface in the reaction vessel was fixed at 8 cm to ensure consistent illumination conditions in each experiment. The temperature of the reaction system was controlled by circulating cooling water in the reactor jacket. Experimental procedure: 10 mg of catalyst was dispersed in 50 mL of chloroquine phosphate (CQ) contaminant solution. The solution was magnetically stirred for 60 min under light-protected conditions to reach adsorption-desorption equilibrium. The light source was then turned on to initiate the reaction. At preset time points, 1.0 mL of the suspension was collected, filtered through a 0.22 μm filter membrane, and analyzed for concentration. The concentration of H2O2 generated in situ during photocatalysis was determined by iodometric titration. HPLC (wavelength 342 nm, C18 column, 4.6 mm × 250 mm, 5 μm) was used. Mobile phase: 40:60, v / v, acetonitrile: 0.3% triethylamine, flow rate: 1.0 mL / min. -1 The concentration of CQ was determined by column temperature (25℃), the amount of Fe dissolved in the reaction solution was tested by ICP-MS, and the concentration of organic carbon in the solution after the reaction was tested by total organic carbon analyzer and the mineralization rate was calculated.

[0055] To demonstrate the effectiveness of the present invention, the following comparative examples were provided: Comparative Example 1: RF resin + Fc 0.40 g of resorcinol, 0.54 mL of oxalic acid solution, and 0.56 mL of formaldehyde solution (37 wt%) were added to 40 mL of aqueous solution and stirred continuously at 400 rpm for 2 h to ensure uniform dispersion. The mixture was then transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete polymer crosslinking. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product was collected by filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h. In the photocatalytic degradation experiment, 1 mg of ferrocene was added, and the rest of the procedure was the same as usual. The H2O2 production and degradation performance were tested.

[0056] Comparative Example 2: Fc + H2O2 Disperse 10 mg Fc in 50 mL of chloroquine phosphate solution (50 mg / L). Add H2O2 (initial concentration 10 μmol), otherwise follow the standard procedure.

[0057] The cumulative H2O2 generation rate, CQ degradation rate, degradation time, and Fe leaching amount of the samples obtained in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1. Table 1 Performance of Examples 1-4 and Comparative Examples 1-2 Table 1 shows that the degradation of CQ is positively correlated with the steady-state concentration of H2O2, indicating that the degradation efficiency in the photo-self-Fenton system is determined by the steady-state concentration of H2O2. Since H2O2 is generated and consumed simultaneously, the decomposition rate constant for Example 1 was calculated to be 0.015 min. -1 The intrinsic cumulative H2O2 formation rate is estimated to be 2330 μmol·g. -1 ·h -1 The balance between H2O2 generation and activation rate is precisely what enhances the photo-Fenton efficiency, enabling the efficient degradation of organic pollutants in a short time. Ferrocene was dispersed in water as an activator for photocatalytic performance testing (Example 5). The results showed that the cumulative H2O2 generation in the system decreased, and the CQ degradation performance was reduced, resulting in poor mineralization. This may be because the distance between the H2O2 generation site and the activation site is large, and H2O2 is ineffectively consumed during diffusion to the activation site, leading to a decrease in photo-Fenton efficiency. Comparative Examples 1 and 2 show that in the presence of an added Fenton activator (Fc) or in the traditional photo-Fenton system, the CQ degradation time is long, the mineralization rate is low, and the amount of iron ions dissolved is greatly increased, causing secondary pollution to the environment, with the content far exceeding the national drinking water standard limit (0.3 mg / L).

[0058] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.

Claims

1. A method for preparing a paramagnetic photo-self-Fenton catalyst, characterized in that, Includes the following steps: Step S1: Ferrocene derivative, formaldehyde and resorcinol are placed in a mixed solvent of ethanol / water in a mass ratio, a catalyst is added, and the mixture is stirred until completely dissolved to obtain a precursor solution. Step S2: The precursor solution is transferred to a high-pressure reactor for solvothermal polycondensation reaction; Step S3: After the reaction is complete, cool to room temperature, filter to collect the solid product, and wash to remove unreacted monomers and oligomers; Step S4: Dry the washed solid to obtain a ferrocene-functionalized paramagnetic photo-self-Fenton catalyst.

2. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, The ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde; the catalyst is one of oxalic acid and acetic acid, and the amount used is 0.1-0.3% of the mass of resorcinol.

3. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, The ratio of ethanol to water in the mixed solvent is 1:5 to 1:

15.

4. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, The ferrocene derivative accounts for 1%-10% of the total mass of the reactants; the mass ratio of the ferrocene derivative to resorcinol is 1:5-1:30; and the mass ratio of resorcinol to formaldehyde is 1:

2.

5. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, In step S2, the temperature of the solvothermal polycondensation reaction is 250℃, and the time is 6-24h.

6. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, In step S3, the washing process involves washing with deionized water and ethanol 3-5 times in sequence.

7. The method for preparing the paramagnetic photo-self-Fenton catalyst according to claim 1, characterized in that, In step S4, the drying process is carried out under vacuum conditions at 60-100℃ for 8-24 hours.

8. A paramagnetic photo-self-Fenton catalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. An application of the paramagnetic photo-self-Fenton catalyst as described in claim 8, characterized in that, The paramagnetic photo-self-Fenton catalyst is dispersed in an aqueous solution containing organic pollutants. Under visible light or sunlight irradiation, the catalyst generates H2O2 in situ and is simultaneously activated to produce hydroxyl radicals, thereby degrading organic pollutants through a photo-self-Fenton reaction.

10. The application according to claim 9, characterized in that, The organic pollutants include dyes, antibiotics, phenols, and pesticides.